2017
DOI: 10.1371/journal.pone.0183097
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of colon carcinogenesis by Blastocystis sp.

Abstract: Colorectal cancer (CRC) is one the most commonly diagnosed cancers worldwide and the number is increasing every year. Despite advances in screening programs, CRC remains as the second leading cause of cancer deaths in the United States. Oxidative stress plays an important role in the molecular mechanisms of colorectal cancer (CRC) and has been shown to be associated with Blastocystis sp., a common intestinal microorganism. In the present study, we aimed to identify a role for Blastocystis sp. in exacerbating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 60 publications
(70 reference statements)
1
35
0
1
Order By: Relevance
“…infected AOM-rats compared to the AOM-treated controls. Higher levels of advanced oxidative protein products (AOPP) were also found in the serum [150], which is concordant with high plasma AOPP levels found in CRC patients compared to healthy individuals [151].…”
Section: Disruption Of Gut Bacteria Composition As Internal Pathogenisupporting
confidence: 69%
See 1 more Smart Citation
“…infected AOM-rats compared to the AOM-treated controls. Higher levels of advanced oxidative protein products (AOPP) were also found in the serum [150], which is concordant with high plasma AOPP levels found in CRC patients compared to healthy individuals [151].…”
Section: Disruption Of Gut Bacteria Composition As Internal Pathogenisupporting
confidence: 69%
“…was isolated from fecal samples and inoculated into rats treated with the carcinogen, azoxymethane (AOM), Blastocystis sp. co-treatment, and a control group [150]. Histologically, AOM-treated rats with co-administration of Blastocystis sp.…”
Section: Disruption Of Gut Bacteria Composition As Internal Pathogenimentioning
confidence: 99%
“…has a significant role in enhancing Azoxymethane (AOM) -induced carcinogenesis damage to the intestinal epithelium and oxidative damage were observed in rats infected with Blastocystis sp and the study proposed that Blastocystis sp. is a pathogen protozoa so it is necessary to screen cancer patients for this parasite (Kumarasamy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that oxidative stress plays a critical role in the molecular mechanisms of colorectal cancer (CRC) and is shown to be associated with Blastocystis sp, that is the most common intestinal protozoa (Kumarasamy et al, 2017). The pathogenicity of Blastocystis sp.…”
Section: Prevalence Of Intestinal Parasitic Infection In Cancer Orgamentioning
confidence: 99%
“…More recently, El-Gayar and Mahmoud (2014), Mohamed et al (2017) and Kumarasamy et al (2017) speculated potential carcinogenic effect of Blastocystis sp. as the parasite affected the growth of colorectal cancer cells in vitro (Chandramathi et al 2010) and induced precancerous polyp formation in vivo in rats (Kumarasamy et al 2017).…”
Section: Introductionmentioning
confidence: 99%